2015
DOI: 10.1080/17441692.2014.986178
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health: Progress and outstanding needs

Abstract: We examine progress towards the 1994 International Conference on Population and Development (ICPD) commitment to provide universal access to sexual and reproductive health (SRH) services by 2014, with an emphasis on changes for those living in poor and emerging economies. Accomplishments include a 45% decline in the maternal mortality ratio (MMR) between 1990 and 2013; 11.5% decline in global unmet need for modern contraception; ~21% increase in skilled birth attendance; and declines in both the case fatality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 86 publications
1
49
0
Order By: Relevance
“…Germain, Dixon-Mueller, and Sen (2009) showed that systematic separation, through funding and other mechanisms, of HIV/AIDS from the broader SRHR agenda served to weaken the latter even though systemic reforms towards greater accountability were pursued by the GFATM and others. Snow et al (2014) documents persistent inequalities in access to SRHR causing harm especially to women in the lowest two wealth quintiles, with 'key services … in shockingly short supply'. Furthermore, indirect evidence on HIV-and abortion-related and maternal deaths of adolescents suggests widespread gaps in access to health care (Chopra, Daviaud, Pattinson, Fonn, & Lawn, 2009;Houweling, Ronsmans, Campbell, & Kunst, 2007;Rashid, Akram, & Standing, 2011;Tilahun, Mengistie, Egata, & Reda, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Germain, Dixon-Mueller, and Sen (2009) showed that systematic separation, through funding and other mechanisms, of HIV/AIDS from the broader SRHR agenda served to weaken the latter even though systemic reforms towards greater accountability were pursued by the GFATM and others. Snow et al (2014) documents persistent inequalities in access to SRHR causing harm especially to women in the lowest two wealth quintiles, with 'key services … in shockingly short supply'. Furthermore, indirect evidence on HIV-and abortion-related and maternal deaths of adolescents suggests widespread gaps in access to health care (Chopra, Daviaud, Pattinson, Fonn, & Lawn, 2009;Houweling, Ronsmans, Campbell, & Kunst, 2007;Rashid, Akram, & Standing, 2011;Tilahun, Mengistie, Egata, & Reda, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dilation and curettage requires trained, skilled health personnel, management that may consequently place an additional burden on a struggling workforce. MVA, when undertaken in the first trimester, is quicker and associated with less blood loss when compared to dilatation and curettage [30].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study within the settlements in Port Moresby, the Capital of PNG, identified childbirth as a leading cause of death (3/53; 5.7%). All maternal deaths were the result of poor transport systems [30]. Through a maternal mortality review in 2010, Kirby [29] linked maternal deaths in remote, rural areas of Milne Bay Province to the three delay framework, [31] described in Chapter Two of this thesis.…”
Section: Causes and Timing Of Maternal Deathsmentioning
confidence: 99%
See 2 more Smart Citations